Towards 100 % recycling of reclaimed asphalt in road surface courses: binder design methodology and case studies - Lo Presti, Davide; Jiménez del Barco Carrión, Ana; Airey, Gordon; Hajj, Elie (Elsevier, 2016)
Reclaimed Asphalt (RA) has shown great potential to be reused in new asphalt mixtures, however its incorporation in top asphalt pavement layers is still very limited (10-30%). In fact, despite the advantages that its use implies, RA content in road pavement surface courses is still restricted in most countries due to mainly legislation limitations, but also some technical issues. This paper aims at being a step further to improve the latter by providing a methodology that allows producing fundamental inputs for confidently performing mix design of asphalt mixtures incorporating up to 100% RA. The methodology consists in an advanced preliminary binder’s blend design that can be used with any type of RA and also in presence of rejuvenators. This procedure includes in the production of blending charts and laws that considers the uncertainties on accounting the extent of final binder content, Degree of Blending and Replaced Virgin Binder. The description of the methodology is accompanied with results of two extreme case studies consisting in the preliminary design of binders for asphalt mixtures with high content of two types of RA corresponding to extreme cases: the short-term aged RA (STA-RA), having a very soft residual binder (Pen> 20dmm) and the long-term aged RA, having a much harder residual binder (Pen <10dmm). As a result, the proposed methodology allowed assessing the feasibility of using up to 90% of RA and determining whether the use of rejuvenating agents was needed.